Предмет: Алгебра,
автор: Alena100499
0,5х - 3* ( 1/5х - 4) + 1/6 * ( 15х -1) Упростите выражение.
Ответы
Автор ответа:
0
0,5х - 3* ( 1/5х - 4) + 1/6 * ( 15х -1)=0,5x-3x/5+12+(15x)/6-1/6=(1/2-3/5+15/6)x+11 5/6=((15-6+75)/30)x+11 5/6=84/30x+11 5/6=2 24/30x+11 5/6=2 4/5x+11 5/6
через пробел указана дробная часть числа (11 целых пять шестых)
Похожие вопросы
Предмет: Английский язык,
автор: adk49309
Предмет: История,
автор: nb6765
Предмет: Математика,
автор: xorosho10000
Предмет: История,
автор: Таннека
Предмет: Математика,
автор: Горошко